Organizational reward system and job satisfaction among non-academic staff at Universiti Malaysia Sabah - Dean Nelson Mojolou; Helmina Thomas; Toh, Pei Sung; Faerozh Madli (Asian Academy of Applied Business, 2023)
The paper aims to investigate the relationship between intrinsic and extrinsic reward systems and job satisfaction among non-academic employees at the University of Malaysia Sabah. The researchers used survey questionnaires and secondary data to collect and gather information. The response rate was 51.4% (n=72), and the questionnaire was usable. The data were collected using a convenient sampling technique and analyzed using SPSS 23.0 and smart PLS (Partial Least Square) version 2.0. The result indicates that 0.615 (61.5%) of the variance in job satisfaction is explained by all the two constructs of intrinsic and extrinsic. There were three hypotheses tested. All hypotheses were strongly supported. The result shows that this organization's relationship between the reward system and job satisfaction is significant. The extrinsic reward system has the greatest influence on job satisfaction. Extrinsic rewards such as yearly bonuses can make the workers feel happy and motivate them to work harder in the future. Any organization should be more concerned with extrinsic reward systems such as salary, bonuses, and any outdoor activity that can show appreciation to the employees to boost their job satisfaction.